THE ROLE OF SOCIAL MEDIA MARKETING IN BUILDING CUSTOMER EQUITY- SPECIAL REFERENCE TO TRAVEL AND TOURISM INDUSTRY IN SRI LANKA - Dhanushanthini, A. (University of Jaffna, 2019)
Due to its dynamic and emergent nature, the effectiveness of social media as a marketing communication channel has presented many challenges for marketers and more consumers are using them as a source of information about products, services and brands. On the other hand, the value a customer brings to a firm is not limited to the profit from each transaction but is the total profit the customer may provide over the duration of the relationship with the firm. Thus, customer equity has been considered as the most determinant of the long-term values of the firm. Based on that this study examined the research problem of whether the social media marketing (SMM) impacts on customer equity in Travel and Tourism Industry (TTI) in Sri Lanka. The objective of this study is to identify the impact of SMM on customer equity in Sri Lankan TTI. Furthermore, the conceptual model has been developed to link SMM and customer equity. Entertainment, interaction, trendiness, customization and word of mouth are considered as the dimensions of SMM. Similarly, value equity, brand equity and relationship equity are the dimensions of customer equity which were extracted from literature. Questionnaire was used to collect data. Fifteen, tourist hotels have been selected in Colombo District based on non-probability sampling method (quota sampling method). Multiple regression analysis has been used for the analysis. Findings revealed that there is a positive impact of SMM on customer equity in Sri Lankan Travel and Tourism Industry.
Keywords: customer equity; social media marketing; travel and tourism industry; Sri Lanka